Comparative Study of Magnetic Levitation Models - Raut, N. K.; Miller, J.; Chiao, R. Y.; Sharping, J. E. (Journal of Nepal Physical Society, 2022)
Levitation refers to free flotation, where the levitated object is suspended freely, against gravity without any physical contact. Among many levitation, magnetic levitation due to a finite-sized type-I superconductor was demonstrated and characterized. Here, we have developed a model by extending the two-loop method to calculate the levitation height for magnetic levitation within the superconducting microwave cavity and is compared with widely used mirror and finite-size superconductor method. The models were used to calculate the levitation height from the center and edge of the superconductor for magnet with strength 0.1 - 2.0 T. We observed a large discrepancy between the models for the edge levitation where our model underestimate the levitation height by 40-95%. Furthermore, in contrast to other models, our model has shown a superior capacity to calculate the levitation height at any location on the superconductor